Digital Natives, Virtual Leaders: A Systematic Review of Digital Capability and Virtual Leadership Impact on Generation Z Remote Work Performance - Munawaroh Munawaroh; Siti Nursyamsiyah AR; Suryadi Fadillah; Amrullah Amrullah; Risti Risti (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Digital transformation and accelerating remote work adoption fundamentally reshape organizational human resource management, particularly for Generation Z employees characterized by digital fluency yet varying professional digital competencies. This systematic literature review examines digital capability and virtual leadership roles influencing Generation Z remote employee performance through comprehensive synthesis of empirical research published 2020-2025. Following PRISMA guidelines, systematic search across academic databases identified 45 relevant peer-reviewed articles analyzed thematically. Findings reveal digital capability significantly enhances remote work effectiveness through technological adaptation, digital system utilization, and information literacy, while virtual leadership influences performance through online communication quality, coordination clarity, trust-building, and virtual engagement. Crucially, both constructs demonstrate complementary rather than independent effects—digital capability provides foundational competencies enabling remote task execution, while virtual leadership ensures strategic direction and supportive environment maximizing capability utilization. Research contributes integrated conceptual framework positioning these factors as strategic imperatives for Generation Z remote work management, offering empirical foundation for organizational policy development. Findings guide human resource practitioners designing digital-age workforce strategies balancing technological infrastructure investment with adaptive leadership development, addressing critical gap in Generation Z-specific remote work performance literature